Selective tuberculosis incidence estimation by digital computer information technologies in the MS Excel system - G. I. Ilnitsky (Туберкулез и болезни лёгких, 2014)
The incidence of tuberculosis was estimated in different age groups of people, applying the digital computer information technologies of tracking. For this, the author used the annual forms of the reporting materials stipulated by the Ministry of Health of Ukraine, the results of his observations, and the data of bank information accumulation in the MS Excel system. The initial positions were formed in terms of the epidemiological indicators of Ukraine and the Lvov Region during a 10-year period (2000-2009) that was, in relation with different initial characteristics, divided into Step 1 (2000-2004) in which the tuberculosis epidemic situation progressively deteriorated and Step 2 (2005-2009) in which relative morbidity was relatively stabilized. The results were processed using the MS Excel statistical and mathematical functions that were parametric and nonparametric in establishing a correlation when estimating the changes in epidemic parameters. The findings of studies among the general population could lead to the conclusion that the mean tuberculosis morbidity in Ukraine was much greater than that in the Lvov Region irrespective of the age of a population. At the same time, the morbidity rate in the foci of tuberculosis infection suggested that it rose among both the children, adolescents, and adults, which provided a rationale for that therapeutic and preventive measures should be better implemented.